2018
DOI: 10.3389/fmed.2018.00062
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Spondyloarthritis

Abstract: Comorbidities in spondyloarthritis (SpA) add to the burden of disease by contributing to disease activity, functional and work disability, and mortality. Thus, awareness of comorbidities in SpA is crucial to improve their screening and management and to ultimately improve outcomes in those affected. Osteoporosis has been reported to be the most prevalent comorbidity in SpA, and its risk is increased in these patients, compared with the general population; the risk of vertebral fractures requires further evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 121 publications
1
57
0
3
Order By: Relevance
“…Patients with axSpA frequently have extra-articular manifestationsdincluding uveitis, psoriasis, and inflammatory bowel disease (IBD)dand additional comorbidities associated with axSpA such as fatigue, osteoporosis, cardiovascular disease, and sleep apnea. 19,[31][32][33][34][35][36] The most common extraarticular manifestation in axSpA is anterior uveitis, which affects 25% to 35% of patients. Uveitis in axSpA is typically acute and unilateral and can be self-limited; recurrence is common and may occur in the alternate eye.…”
Section: Recognizing Axial Spondyloarthritismentioning
confidence: 99%
“…Patients with axSpA frequently have extra-articular manifestationsdincluding uveitis, psoriasis, and inflammatory bowel disease (IBD)dand additional comorbidities associated with axSpA such as fatigue, osteoporosis, cardiovascular disease, and sleep apnea. 19,[31][32][33][34][35][36] The most common extraarticular manifestation in axSpA is anterior uveitis, which affects 25% to 35% of patients. Uveitis in axSpA is typically acute and unilateral and can be self-limited; recurrence is common and may occur in the alternate eye.…”
Section: Recognizing Axial Spondyloarthritismentioning
confidence: 99%
“…A number of other conditions can also co-exist with axSpA, classically referred to as comorbidities. These include metabolic bone and cardiovascular disease [6][7][8] which further contribute to the complexity of patients, challenging their management and outcomes. AxSpA has been associated with severe physical limitation, functional impairment and decreased quality of life [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…APOB and APOC were the main protein components of low-density lipoproteins (LDL) and very low density lipoproteins (VLDL), respectively, and they were important biomarkers for predicting the cardiovascular (CV) risks [76]. It has been reported that the CV event is the leading cause of mortality in AS, which is partly due to the dyslipidemia in AS patients, including high levels of APOB and APOC [77]. Previously, Huang et al [78] reported that plasma levels of APOB and APOC markedly decreased in the hyperlipidemia rabbit model and increased following herbal-partitioned moxibustion.…”
Section: Lipid Metabolism Pathwaymentioning
confidence: 99%